Analisis Efektivitas Kebijakan Pemerintah Daerah Kabupaten Buleleng Terkait Pemungutan PBB-P2 Pada Masa Pandemi COVID-19 - Pradiska, Komang Intan; Prayudi, Made Aristia (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
This research aims to find out 1) Forms of Application of Local Government Policies in Buleleng Regency related to the rural and urban property taxes collection, 2) Obstacles faced by Buleleng Regency Government in implementing Buleleng Regency Government Policies Related to Collecting The rural and urban property taxes, 3) Effectiveness of Buleleng Regency Local Government Policies Regarding The rural and urban property taxes Collection during the COVID-19 Pandemic.This researh used descriptive qualitative method. Data collection is done through the method of documentation techniques, interviews and literature studies. The data is then analyzed using data reduction, data presentation to drawing conclusions based on the specified theory. The results of the study show 1) The form of implementation of this policy is the abolition of The rural and urban property taxes administrative sanctions in 2020 and before. 2) Obstacles in implementing the policy, namely the declining ability of the public to pay, the apathy of the community in paying taxes. and Lack of dissemination of information regarding the Policy. 3) The policy is very effective in increasing The rural and urban property taxes revenue.Â Â